The painter's daughter - Klassen, Julie, 1964- (Bethany House, a division of Baker Publishing Group, 2015)
"In 1815, a painter's daughter on the north Devon coast agrees to marry a stranger to avoid scandal, but her choice is complicated by the return of a former lover and a growing affection for the husband she barely knows."--